Dampak Implementasi Akuntansi Berbasis Akrual Terhadap Sistem Informasi Pemerintahan Daerah - Nasrun Naida (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to examine the impact of accrual-based accounting implementation on the Regional Government Information System (SIPD), particularly in the Accounting and Reporting (AKLAP) module, within the Tojo Una-Una Regency Government. The adoption of accrual-based accounting, as mandated by Ministry of Home Affairs Regulation No. 64 of 2013, is intended to enhance the quality of Local Government Financial Reports (LKPD). The research employs a qualitative method using a descriptive approach. Data were gathered through questionnaires, interviews, and direct observations involving 50 respondents from 33 Regional Government Organizations (OPD) in Tojo Una-Una Regency). The findings indicate that the implementation of accrual-based accounting through the SIPD AKLAP module has been successfully carried out across all OPDs, producing a positive effect on the timeliness, relevance, and accuracy of financial reporting. Human resource development and information technology have been identified as key success factors in the effective application of accrual-based accounting. However, certain operational challenges remain and require improvement, particularly in the practical use of the SIPD AKLAP system in daily activities.